2016
DOI: 10.1002/cssc.201600769
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Cobalt/Vanadium Complexes as Precursors for Functionalized Mixed Oxides in Visible‐Light‐Driven Water Oxidation

Abstract: The heterometallic complexes (NH ) [Co(H O) ] [V O ]⋅4 H O (1) and (NH ) [Co(H O) (β-HAla)] [V O ]⋅4 H O (2) have been synthesized and used for the preparation of mixed oxides as catalysts for water oxidation. Thermal decomposition of 1 and 2 at relatively low temperatures (<500 °C) leads to the formation of the solid mixed oxides CoV O /V O (3) and Co V O /V O (4). The complexes (1, 2) and heterogeneous materials (3, 4) act as catalysts for photoinduced water oxidation. A modification of the thermal decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Pavliuk et al designed CoV 2 O 6 /V 2 O 5 and Co 2 V 2 O 7 /V 2 O 5 in TiO 2 films for electrocatalytic O 2 evolution, which showed good stability and sustained high-current densities at relatively low overpotentials [ 32 ]. Shen et al designed a CoV 2 O 6 –V 2 O 5 /NRGO−1 composite for electrochemical WOR with high efficiency in which CoV 2 O 6 acted as an active site [ 33 ]. Recently, Mondal et al established the structure-property relationship of CoV 2 O 6 and Co 3 V 2 O 8 for electrocatalytic O 2 evolution, and the experimental results showed that the former was more active than the latter [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pavliuk et al designed CoV 2 O 6 /V 2 O 5 and Co 2 V 2 O 7 /V 2 O 5 in TiO 2 films for electrocatalytic O 2 evolution, which showed good stability and sustained high-current densities at relatively low overpotentials [ 32 ]. Shen et al designed a CoV 2 O 6 –V 2 O 5 /NRGO−1 composite for electrochemical WOR with high efficiency in which CoV 2 O 6 acted as an active site [ 33 ]. Recently, Mondal et al established the structure-property relationship of CoV 2 O 6 and Co 3 V 2 O 8 for electrocatalytic O 2 evolution, and the experimental results showed that the former was more active than the latter [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time V-based anions are found to be more active in redox processes. 3,4 Mo/V anions usually have the structural types characteristic for polyoxomolybdates and the introduction of easily-reducible V-centers into a POM may change the nature of products from purely acidic to redox. Moreover, the redox properties can be tuned by the number of V-centers in the clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] This paper is a continuation of our research devoted for the synthesis of hybrid compounds based on POMs under mild conditions. 3,4,[28][29][30] Our work is focused on the study of inuence of synthetic conditions such as the stoichiometry of reagent, metal sources in the reaction mixtures and the time of interaction. Previously…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high costs and low abundance of these metals, there is considerable interest in the use of cheap base metal complexes for water oxidation. To date, a handful of cobalt,20 manganese,21,22 copper,23 nickel24 and iron compounds have been studied with respect to their potential as WOCs. However, iron, being the most abundant and cheap transition metal, is the least used in molecular WOCs, arguably due to the low stability of iron complexes under oxidative conditions.…”
Section: Introductionmentioning
confidence: 99%